The Legacy of Mary Scranton - Kwon, Andrea (International bulletin of mission research, 2018)
Mary Scranton was an American missionary to Korea, the first missionary sent there by the Woman's Foreign Missionary Society (WFMS) of the Methodist Episcopal Church. During her more than two decades of service, Scranton laid the foundations for the WFMS mission in Seoul and helped to establish the wider Protestant missionary endeavor on the Korean peninsula. Her pioneering evangelistic and educational work, including the opening of Korea's first modern school for girls, reflected Scranton's commitment to ministering to and with Korean women.